CD40-Mediated Activation of the NF-κB2 Pathway - Bishop, Gail A.; Hostager, Bruce S. (Frontiers in Immunology, 2013)
CD40 is a critical stimulatory receptor on antigen-presenting cells of the immune system. CD40-mediated activation of B cells is particularly important for normal humoral immune function. Engagement of CD40 by its ligand, CD154, on activated T cell membranes initiates a variety of signals in B cells including activation of MAP kinases and NF-B. The transcriptional regulator NF-B is in reality a family of factors that can promote B cell activation, differentiation, and proliferation. Complex and only partially understood biochemical mechanisms allow CD40 to trigger two distinct NF-B activation pathways, canonical (NF-B1) and non-canonical (NF-B2) NF-B. This brief review provides a summary of mechanisms responsible for activation of the latter, which appears to be particularly important for enhancing B cell viability at various stages in their life cycle and may also contribute to development of B cell malignancies. CD40 is also expressed by various cell types in addition to B cells, including T cells, macrophages, dendritic cells, and certain non-hematopoietic cells. Here too, while perhaps less extensively studied than in B cells, the CD40-mediated activation of NF-B2 appears to have important roles in cellular physiology.